2015
DOI: 10.1093/rpd/ncv411
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Audit of Image Quality in Radiology Using Visual Grading Characteristics Analysis

Abstract: The aim of this work was to assess whether an audit of clinical image quality could be efficiently implementedwithin in a limited time frame using visual grading characteristics (VGC) analysis.Lumbar spine radiography, bedside chest radiography and abdominal CT were selected. For each examination, images were acquired or reconstructed in two ways. Twenty images per examination were assessed by 40 radiology residents using visual grading of image criteria. The results were analysed using VGC. Inter-observer rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…In another study of image quality Tesselaar et al compared lumbar spine radiographs in two different settings: Sensitivity class 400 (less noise) and sensitivity class 560 (more noise). They concluded that higher image quality produced higher inter-observer reliability, AC1 = 0.72 vs. 0.57 [14]. This is relevant to point out, since we, for economic reasons, used an open source image viewer for all image assessments.…”
Section: Discussionmentioning
confidence: 99%
“…In another study of image quality Tesselaar et al compared lumbar spine radiographs in two different settings: Sensitivity class 400 (less noise) and sensitivity class 560 (more noise). They concluded that higher image quality produced higher inter-observer reliability, AC1 = 0.72 vs. 0.57 [14]. This is relevant to point out, since we, for economic reasons, used an open source image viewer for all image assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Visual grading analysis permits an image or parts of an image to be evaluated visually and has been validated in human radiology, as an analytical system for image quality . Using predefined imaging criteria allows the quantification of subjective opinions into a scoring system making them amenable to statistical analysis .…”
Section: Discussionmentioning
confidence: 99%
“…It is dependent on the readers' ability to detect and correctly interpret the visible pathology. For the above reasons a standard ROC study is a time-consuming and costly method that requires a large number of cases to produce statistically significant results and may not be a practical choice for optimisation purposes [58].…”
Section: Receiver Operating Characteristic (Roc)mentioning
confidence: 99%
“…iii. Participating observer time workload is moderate, hence multiple observers can participate leading to an increase in statistical power of the result [58,60]. iv.…”
Section: Visual Grading Experimentsmentioning
confidence: 99%
See 1 more Smart Citation